Spin-echo nuclear magnetic resonance for tissue characterisation in arrhythmogenic right ventricular cardiomyopathy. Issue 6 (December 1996) - Menghetti, L.; Basso, C.; Nava, A.; Angelini, A.; Thiene, G.
Abstract : OBJECTIVE: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a myocardial disorder characterised clinically by ventricular arrhythmias that can cause cardiac arrest and morphologically by fatty or fibro-fatty myocardial atrophy of the right ventricle. In vivo tissue characterisation without endomyocardial biopsy would be useful. The aim of this study was to investigate the diagnostic accuracy of spin-echo nuclear magnetic resonance (NMR) for tissue characterisation in ARVC. PATIENTS AND METHODS: Twenty three subjects (15 men and eight women, aged 18-49, mean 34) were studied with spin-echo T1-weighted NMR and multislice scan. Fifteen had a clinical diagnosis of ARVC and eight were controls (age and sex matched subjects). Data were independently evaluated by two expert observers. RESULTS: In the control group NMR was always negative (100% specificity). Ten of the 15 patients with ARVC had an abnormal NMR result (67% sensitivity), with areas that had a signal intensity close to that of pericardial or subcutaneous fat. In the remaining five cases the NMR signal was inadequate. Nine patients underwent both NMR and endomyocardial biopsy; biopsy was positive in eight (89%) and NMR was positive in five (56%). CONCLUSIONS: NMR is a useful non-invasive diagnostic tool in the evaluation of fatty replacement in ARVC. The technique can be used with other procedures in the initial diagnostic evaluation and is a useful alternative tool in the long term follow up of patients with ARVC.